The Effect of Career Adaptability and Social Support toward Student Careerself-Efficacy - Murviana Koto; Hastina Febriaty; Satria Mirsya Affandi Nasution (AIBPM Publisher, 2019)
In conditions of high competition to find a job, students need to make career preparations as early as possible. Career preparation is begun with making decisions about the career they want to get. Then in making preparations, they need the ability to adapt to the chosen career. In addition, the social support is also needed. This study was conducted on students in one of the private university in Medan, Sumatera Utara. The test results by using the Structural Equation Model (SEM) showed that there were significant positive relationship between the ability of career adaptability and social support with career decision-making self-efficacy. It also concluded that social support partially mediates the relationship between career adaptability and career decision- making self-efficacy.